Selected poems - Tuwim, Julian 1894-1953 (Brandl & Schlesinger, 2017)
"Julian Tuwim (1919-1953) was a Polish poet, writing cabaret sketches, humoresque pieces, satires, and comic pieces rooted in and alluding to Jewish tradition. His phrases would echo in the Warsaw streets. He wrote texts for the theatre and librettos for opera, as well as lyrics to musical hits of his era and film soundtracks. Tuwim's oeuvre was a veritable poetic firework during the 20s and 30s of the last century. It's a triumph of innovation and emotional courage. This extraordinary poetic phenomenon found an equally extraordinary interpreter/translator who has managed to bring to the international stage this surprisingly modern -- or even post-modern -- poetic endeavour full of exuberance and energy."
Keywords: Polish poetry / 20th century; Polish poetry / Translations into English; Polish poetry; 1900-1999; Poetry; Translations; Anthologie